2019
DOI: 10.1177/2309499019835651
|View full text |Cite
|
Sign up to set email alerts
|

Return to sports after chronic anterior exertional compartment syndrome of the leg: Conservative treatment versus surgery

Abstract: Aim: To evaluate whether surgical treatment for anterior chronic exertional compartment syndrome (CECS) of the lower leg will lead to full athletic activity recovery compared to conservative treatment. Methods: Patients diagnosed with anterior CECS of the leg were offered surgical treatment, as surgery considered today to be the mainstay of treatment. Patients unwilling to be treated surgically were treated conservatively. They were followed up, assessing both groups for pain, functional status, and the Tegner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 27 publications
0
17
1
Order By: Relevance
“…No significant difference in return to physical activity after treatment was found in the current study population. In contrast, earlier studies revealed a higher return to activity rate after surgical treatment compared to conservative treatment [23,24]. Interest-ingly, our results showed a trend towards a higher return rate among conservatively treated patients (conservative 83 % vs. surgery 74 %).…”
Section: Discussioncontrasting
confidence: 96%
See 2 more Smart Citations
“…No significant difference in return to physical activity after treatment was found in the current study population. In contrast, earlier studies revealed a higher return to activity rate after surgical treatment compared to conservative treatment [23,24]. Interest-ingly, our results showed a trend towards a higher return rate among conservatively treated patients (conservative 83 % vs. surgery 74 %).…”
Section: Discussioncontrasting
confidence: 96%
“…The three different types of lower leg CECS, including combinations, were not separately evaluated. Our study design is different from previously published cohorts focusing on the anterior compartment only [22][23][24]. For instance, the study by Packer et al [23] found higher satisfaction rates in patients only receiving a fasciotomy for the anterior compartment compared to patients undergoing surgery for multiple compartments.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…More recent studies have done the same and have included measures such as the Tegner activity scale, SF-12, and the Euro-Qol-5D index score. 2,8,23 Future studies looking at the operative treatment of CECS may continue to include these additional outcome measures to more accurately compare results of treatment techniques and develop a more standardized definition of success in the treatment of CECS. Based on the outcome data from this retrospective study, a power analysis for a future prospective study (2group design) was performed to better delineate the sample size required to reach a clinically significant conclusion when using these validated patient outcome measures.…”
Section: Discussionmentioning
confidence: 99%
“…More recent studies have done the same and have included measures such as the Tegner activity scale, SF-12, and the EuroQol-5D index score. 2 , 8 , 23 Future studies looking at the operative treatment of CECS may continue to include these additional outcome measures to more accurately compare results of treatment techniques and develop a more standardized definition of success in the treatment of CECS.…”
Section: Discussionmentioning
confidence: 99%